Advances in Chemical Physics, Single Molecule Biophysics : Experiments and Theory. - Komatsuzaki, Tamiki (Advances in chemical physics., 2011)
Discover the experimental and theoretical developments in optical single-molecule spectroscopy that are changing the ways we think about molecules and atoms The Advances in Chemical Physics series provides the chemical physics field with a forum for critical, authoritative evaluations of advances in every area of the discipline. This latest volume explores the advent of optical single-molecule spectroscopy, and how atomic force microscopy has empowered novel experiments on individual biomolecules, opening up new frontiers in molecular and cell biology and leading to new theoret.